Level of Awareness and Susceptibility to Phishing Attacks Among Students of Quezon City University: A Stratified Survey Study (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Phishing attacks continue to pose serious cybersecurity risks in educational institutions as students increasingly rely on digital platforms for academic and personal activities. This study aimed to determine the level of phishing awareness and phishing susceptibility among students of Quezon City University, particularly comparing IT and non-IT students. Using a descriptive-comparative quantitative research design, data were collected from 397 students through a stratified survey conducted using online and printed questionnaires. Statistical tools such as frequency and percentage, weighted mean, independent samples t-test, and Pearson Product-Moment Correlation Coefficient were used to analyze the data. The findings revealed that students generally demonstrated a high level of phishing awareness but showed a moderate level of phishing susceptibility. Results also indicated a significant difference in phishing awareness between IT and non-IT students, with IT students exhibiting higher awareness levels. However, no significant difference was found in phishing susceptibility between the two groups. Furthermore, a significant moderate negative relationship was identified between phishing awareness and phishing susceptibility, indicating that higher awareness is associated with lower vulnerability to phishing attacks. The study concludes that although students possess adequate knowledge regarding phishing threats, awareness alone does not completely prevent risky online behavior. The findings may contribute to the development of targeted cybersecurity awareness programs and safer digital practices among university students.